2010
DOI: 10.3109/10428191003763468
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of therapy-related myeloid neoplasms with high-dose cytarabine/mitoxantrone followed by hematopoietic stem cell transplant

Abstract: Few clinical protocols have focused on patients with therapy-related myeloid neoplasms (t-MN). Therefore, we enrolled 32 patients with previously untreated t-MN on a clinical trial testing the effectiveness of a unified induction regimen of high-dose cytarabine and mitoxantrone. The complete remission (CR) rate was 66% (95% CI 47-81%) and the partial remission (PR) rate was 16% (95% CI 5-33%), for an overall response rate of 82%. Day 30 treatment mortality was 9% (3/32), and the most serious induction toxicity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…In the same report, the results of 13 different studies including a total of 496 patients with t‐AML were summarized, revealing an overall CR rate of 27% (Kantarjian et al ., 1993). However, the University of Chicago group recently reported an overall remission rate of 82% with high‐dose cytarabine/mitoxantrone in previously untreated patients with t‐MNs (Godley et al ., 2010). For patients who developed t‐MNs with favourable karyotypes – APL with t(15;17) and core‐binding factor leukaemias with either t(8;21) or inv16/t(16;16) – treatment is recommended with high‐dose chemotherapy in accordance with guidelines for their de novo counterparts.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…In the same report, the results of 13 different studies including a total of 496 patients with t‐AML were summarized, revealing an overall CR rate of 27% (Kantarjian et al ., 1993). However, the University of Chicago group recently reported an overall remission rate of 82% with high‐dose cytarabine/mitoxantrone in previously untreated patients with t‐MNs (Godley et al ., 2010). For patients who developed t‐MNs with favourable karyotypes – APL with t(15;17) and core‐binding factor leukaemias with either t(8;21) or inv16/t(16;16) – treatment is recommended with high‐dose chemotherapy in accordance with guidelines for their de novo counterparts.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…In vivo and in vitro evidence suggest synergistic activity against leukemic cells by combining selinexor with anthracyclines or DNA-damaging agents [ 13 ]. The combination of high-dose cytarabine (HiDAC) with the anthracycline mitoxantrone (Mito) is an effective induction regimen for patients with AML [ 14 17 ] and is frequently utilized at the University of Chicago as frontline therapy for patients with high-risk AML, either de novo or relapsed/refractory. The HiDAC/Mito regimen demonstrated an overall response rate (ORR) of 55% in the high-risk AML population at this institution [ 16 ] and an ORR of 82% in another study of previously untreated patients with therapy-related myeloid neoplasms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fatal course of t-MDS/AML is due to profound and persistent cytopenias due to ineffective hematopoiesis regardless of the fraction of immature blasts accumulating in the bone marrow [61] . In contrast, a subsequent study reported a surprisingly high CR rate of 82% for t-MDS/AML treated with high-dose cytarabine + mitoxantrone [62] . For therapy-related acute promyelocytic leukemia (t-APL) and t-AML with good-risk cytogenetics, specifically inv(16) and t(8;21), induction chemotherapy is recommended, similar to the treatment guidelines for their de novo counterparts [28] .…”
Section: Conventional Chemotherapymentioning
confidence: 89%